Climate impacts and oceanic top predators: Moving from impacts to adaptation in oceanic systems - Hobday, A.; Young, J.; Abe, O.; Costa, D.; Cowen, R.; Evans, K.; Gasalla, M.; Kloser, Rudy; Maury, O.; Weng, K. (Springer, 2013)
Climate impacts are now widely reported from coastal marine systems, but less is known for the open ocean. Here we review progress in understanding impacts on large pelagic species presented at an international workshop for the Climate Impacts on Oceanic Top Predators programme, and discuss the future with regard to the next phase of adaptation-focused research. Recent highlights include a plan to map the distribution of key species in the foodweb using both acoustics and biochemical techniques, and development of a new data sharing and access tool for fisheries and associated data, including socio-economic information. A common research focus in pelagic ecosystems is on understanding climate variability and climate change impacts on marine species, but a greater emphasis on developing future scenarios and adaptation options is needed. Workshop participants also concluded that engagement with and provision of science support to regional fisheries management organisations are critical elements for ensuring successful uptake of research. This uptake will be required for future management of fisheries as global warming continues such that some open ocean top predators can be sustainably harvested, impacts on conservation-dependent species can be avoided, and ecosystem function is not compromised. © 2013 Springer Science+Business Media Dordrecht.